EXTH-49. BXQ-350 TARGETS TO THE LYSOSOME AND KILLS GLIOBLASTOMA (GBM) CELLS VIA ACTIVATION OF APOPTOTIC CASPASES IN VITRO. (9th November 2020) - Wilkins, Nikhil; Stephens, Timothy; Felix, Laura
Abstract: BACKGROUND: Apoptosis is a programmed cell death mechanism where cells respond to internal or external stimuli by initiating a cascade of events and enzymes leading to cell death. One of the hallmarks of cancer is the ability to resist apoptotic stimuli. Removing resistances to apoptosis can result in the death of these tumor cells. METHOD: The GBM cell line Gli36ΔEGFR was used to determine Caspase activity and BXQ-350 cytotoxicity. Cells were treated with 9uM to 30uM BXQ-350 in triplicate and incubated for 24 hours at 37 o C. Promega's Caspase-Glo 9 or Caspase-Glo 3/7 reagent was added to each well of a plate and was incubated at room temperature in the dark for 3 hours then luminescence was read. The parallel cytotoxic assay was run under the same conditions except Roche's MTT labeling reagent was added to each well after 24 hours and the plate was incubated at 37 0 C for 4 hours. Solubilization solution was added to each well, the plate was incubated overnight then absorbance was read. The GBM cell line U87 MG was used to determine lysosomal targeting by treating with 10uM BXQ-350 and incubated at 37 o C overnight. They were stained with anti-SapC (RFP) and anti-LAMP1 (GFP) antibodies and images were taken. RESULT: BXQ-350 mediated cell death is correlated with a rise in Caspase 3, Caspase 7 and Caspase 9 activity. The caspase activity levels did not rise until after BXQ-350 passed its IC50 and stayed elevated. Caspases 3/7 levels showed higher activity compared to untreated than Caspase 9. BXQ-350 was seen to colocalize to LAMP1, a lysosomal membrane protein. CONCLUSION: BXQ-350 tracks to the lysosomal membrane where it initiates a cascade of enzymes necessary to cause apoptosis. Caspases 3/7 are the effector caspases that complete the apoptotic process removing a major barrier to fight cancer.